The fruits of their labor : Atlantic coast farmworkers and the making of migrant poverty, 1870-1945 - Hahamovitch, Cindy (University of North Carolina Press, 1997)
This study consolidates, refines, advances and grounds recent scholarship that challenges familiar platitudes about family farming and rural life in the United States. Its approach yields a depth of information about farming culture not usually found in the literature on rural America. The book takes the reader on a cultural tour of a cherished American institution and landscape: midwestern farm families and their farms.